THE DIFFICULTIES ENCOUNTERED AND STRATEGIES USED BY THE STUDENTS IN WRITING DESCRIPTIVE TEXT - Yaumil Yaumil; Yahya Alaydrus; Dzul Fikri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Descriptive text is a crucial text that must be learned by the students. This article aims at knowing the students’ difficulties in writing descriptive text and the strategies that used by the students to overcome their difficulties in writing descriptive text. The population of this research was the second semester students of English Departemtn at University of Islam Malang. The participants consisted of 34 students. In collecting the data, the researcher used questionnaire as the instrument that covered the difficulties and strategies in writing descriptive text. The finding of this research showed that the students’ biggest problems in writing descriptive text were lack of vocabulary, poor grammar knowledge, organizing idea, developing idea, and generic structure. To overcome these problems, there are some strategies used by the students in writing descriptive text included decide a topic before writing, use a dictionary to chek vocabulary, make an outline, revise a sentence, and share writing with one another.Key Words: Students’ Difficulties and Strategies, Writing, Descriptive Text